2015
DOI: 10.1016/j.jneumeth.2015.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Methyl methacrylate embedding to study the morphology and immunohistochemistry of adult guinea pig and mouse cochleae

Abstract: Our results showed that the Technovit 9100 New(®) embedding system provided highly preserved morphology and immunogenicity with our protocol in adult guinea pig and mouse cochleae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The animals were euthanized 21 days after AG application, while under deep anesthesia using an overdose of Narcoren (4 mL/kg). Then, the cochlear samples were collected, preserved, permeabilized, and blocked, as described previously 84 . The cochlear tissues were stained to detect the CtBP2 (C-terminal-binding protein 2), as described in Supplementary Information.…”
Section: Methodsmentioning
confidence: 99%
“…The animals were euthanized 21 days after AG application, while under deep anesthesia using an overdose of Narcoren (4 mL/kg). Then, the cochlear samples were collected, preserved, permeabilized, and blocked, as described previously 84 . The cochlear tissues were stained to detect the CtBP2 (C-terminal-binding protein 2), as described in Supplementary Information.…”
Section: Methodsmentioning
confidence: 99%
“…While the use of DAPI‐oil is fast and convenient, we observed that even with anti‐fading solution (Vectashield) bleaching of the dye occurred relatively quickly, by observation with UV‐light (∼ 5 min). An aqueous staining approach followed by embedding in anti‐fading solution as reported for methacrylate embedded tissue might provide better results in cases where longer observation times are required (Bako et al ).…”
Section: Assessmentmentioning
confidence: 99%
“…A modification of the previously shown embedding method using a novel polymerization system was used. 29,30 The polymerization system is based on poly(methyl methacrylate). Polymerization occurs in the absence of oxygen and at low temperatures (−2 • C to −20 • C) and enables to perform immunohistochemical staining for hard tissues.…”
Section: Embedding Of Tissue Culture Samplesmentioning
confidence: 99%